Pituitary Abscess: A Rare Clinical Entity in the Presence of Acute Rhinosinusitis: A Case Report - Anagnos, Vincent John; Hanel, Ricardo A.; Naseri, Iman (Journal of Neurological Surgery Reports, 2018)
A pituitary abscess is an often-overlooked diagnosis in the clinical presentation of a sellar mass. Due to its rare incidence and nonspecific presentation, diagnosis and treatment is often delayed. The authors describe a 56-year-old male patient presenting with acute onset of severe headache, visual field deficit, and radiologic findings of an expansile sellar lesion. The presenting symptoms were unremarkable for the diagnosis of meningitis, cavernous sinus thrombosis, and septicemia. Recent medical history included symptoms of rhinosinusitis on the days preceding his acute presentation. The initial clinical presentation was suggestive of a possible pituitary apoplexy. Intraoperative findings revealed purulent output upon surgical entry of the sella. Histopathology confirmed the diagnosis of a pituitary abscess. Review of the clinical and radiologic data revealed evidence of multiple opacifications within the paranasal sinuses, along with dehiscence overlying the sellar bone, supporting a diagnosis of secondary pituitary abscess. This case, along with a review of the available literature, will serve to expand our knowledge of this rare disease process that is often overlooked. Clinicians should be mindful of this condition, and include a primary versus secondary pituitary abscess in the differential workup on such cases.
Keywords: pituitary abscess; rhinosinusitis; acute sinusitis; hypopituitarism; staphylococcal epidermidis; pituitary apoplexy; brain abscess